Towards an ontological reason law in economics: principles and foundations - Francesco Vigliarolo (Insights into Regional Development)
The objective of this article is to propose what can be called a law of ontological reason in economics as opposed to the law of supply and demand. To do this, it uses a phenomenological approach that interprets economics in terms of primary ideas. To this end, it's defined the ontological reason and the space in which it is built in order to introduce the concept of demand of rights and not of consumption. In this context, the relationship that underlies an ontological reason which presupposes a different behavior from that of the law of supply and demand is then described. According to this approach, it is claimed that the latter leads to structural problems. It subordinates the general identity of a country to the interests of individuals, as it focuses on maximizing personal utility that is unrelated to the creation of the rights of men and women living in a context that contains them in a relational way.